1995
DOI: 10.1177/154193129503901303
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cognitive Performance and Stress Perceptions in Military Operations

Abstract: The study reported here is part of a continuing research program investigating the links between psychological stress responses and performance in a variety of settings. A battery of psychological and cognitive measures designed to assess stress perceptions, coping resources, and cognitive performance was administered at selected times in association with the daily test activities of smoke and decontamination platoon operations. During testing soldiers wore the full chemical protective ensemble including mask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In fact, FoF-HR performance improvements were accompanied by a nonsignificantly heightened SNS response, whereas photorealistic target performance improvements were accompanied by a significantly decreasing SNS response. These findings are congruent with the Yerkes-Dodson law (42) and the more recent, dynamic model of stress and sustained attention (12), which state that there is an optimal arousal level for maximum performance, and once that optimal level of arousal or stress has been exceeded, performance then deteriorates (27). The biological rationale behind such a response is to enhance the likelihood of host survival; just as Callaway and Thompson (6) posited, any heightened sympathetic arousal will increase the input threshold of incoming stimuli to prevent sympathetic discharge from running amok.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, FoF-HR performance improvements were accompanied by a nonsignificantly heightened SNS response, whereas photorealistic target performance improvements were accompanied by a significantly decreasing SNS response. These findings are congruent with the Yerkes-Dodson law (42) and the more recent, dynamic model of stress and sustained attention (12), which state that there is an optimal arousal level for maximum performance, and once that optimal level of arousal or stress has been exceeded, performance then deteriorates (27). The biological rationale behind such a response is to enhance the likelihood of host survival; just as Callaway and Thompson (6) posited, any heightened sympathetic arousal will increase the input threshold of incoming stimuli to prevent sympathetic discharge from running amok.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Mullins, Fatkin, Modrow, and Rice (1995) found that participants with less experience reported higher ratings of overall stress. Several other studies have documented the benefits of experience for cognitive performance under stress in NDM situations (Kirschenbaum, 1992;Stokes, 1995;Klein, Calderwood, & ClintonCirocco, 1996;Klein & Calderwood, 1990) .…”
Section: Experience and Trainingmentioning
confidence: 86%